Factors Associated With HIV-Related Stigma Toward People Living With HIV Among Nurses in Liangshan Yi Autonomous Prefecture, China: A Cross-Sectional Study - Yin, Yao; Chen, Angela Chia-Chen; Wan, Shaoping; Chen, Hong (Frontiers in Psychiatry, 2021)
Background: The Liangshan Yi Autonomous Prefecture has one of the most serious human immunodeficiency virus (HIV) epidemics in China. Evidence shows HIV-related stigma toward people living with HIV (PLWH) among nurses impedes HIV prevention and treatment. However, only limited research about HIV-related stigma toward PLWH from the perspective of nurses in Liangshan has been conducted. Objective: This study aimed to assess HIV-related stigma toward PLWH among nurses and determine factors associated with it in Liangshan, China. Design: We conducted a cross-sectional survey using a stratified, random cluster sampling method. Participants: Registered nurses (N=1,248; primary hospitals=102, secondary hospitals=592, tertiary hospitals=554) who were aged 18 or older, worked in the selected hospitals for at least 6 months, and consented to participate were recruited. Methods: All participants completed an anonymous online survey measuring sociodemographic characteristics, HIV-related stigma and HIV knowledge. We used multiple stepwise regression analysis to examine factors associated with HIV-related stigma toward PLWH among these nurses. Results: The mean score of HIV-related stigma among nurses was 50.7 (SD = 8.3; range 25-78). Nurses who were more experienced, had higher levels of education, and were working in tertiary hospitals reported higher level of HIV-related stigma. Those who had better HIV knowledge, reported a willingness to receive HIV-related training, were working in areas that had a high prevalence of HIV, had prior experience working in AIDS specialized hospitals, and worked in hospitals that had policies to protect PLWH showed a lower level of HIV-related stigma toward PLWH. Conclusions: Our findings suggested that providing culturally congruent education and training about HIV and care, and having hospitals that promoted policies protecting PLWH, may reduce HIV-related stigma toward PLWH among nurses in China.